Chronic subdural hematoma associated with fahr syndrome: A clinical association or just a simple coincidence? - Gurcan, Oktay; Gurcay, Ahmet; Kazanci, Atilla; Goker, Tuncer; Eylen, Oguzhan; Turkoglu, Omer (Asian Journal of Neurosurgery, 2018)
The Fahr syndrome (FS) is a rare degenerative neurological disorder (its prevalence is <0.5%). FS is distinguished by the presence of abnormal bilateral intracranial calcifications with a predilection for the basal ganglia, also presented by movement disorders such as parkinsonism, paresis, and speech disorders. Chronic subdural hematoma (CSH), which is typically the result of mild head trauma, is a regularly encountered condition in elderly. A 63-year-old man has referred to our clinic from another hospital with a history of mild head trauma approximately a month ago. At the time of admission, the patient's Glasgow Coma Scale point was 15 points. In the history, there was only mild ataxia and right-sided hemiparesis. The laboratory examination revealed no electrolytes level abnormalities and normal endocrinal test examinations. Computed tomography revealed bilateral calcifications of basal ganglia, dentate nuclei which were misinterpreted as intracerebral contusion; with CSH of left temporal and parietal region. The hematoma was evacuated by burr-hole drainage. The patient was discharged 5 days after the surgery. The pathophysiology of FS is still unrevealed. There are some suggestions such as secondary to local disturbance of blood-brain barrier or a calcium neuronal metabolism disorder. However, on the other hand, local blood-brain barrier disturbance would also take part in CSH pathology. We hypostasized that patients with the history of FS, who had mild head traumas, might prone to subdural collections. On the other hand, FS and CSH coexistence is very unusual. Neurosurgeons might keep in mind FS when bilateral calcifications are seen in a patient.
Keywords: Blood-brain barrier; chronic subdural hematoma; coincidence; Fahr syndrome